Pengaruh Co-Branding terhadap Minat Beli Followers Instagram Kedai Kopi FC - Hilman, Nasywa Khairunnisa; Rachmawati, Erna; Utami, Hesty Nurul; Wiyono, Sulistyodewi Nur; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
FC is one of the coffee shop businesses that actively promotes its products on Instagram. However, in terms of the number of followers and brand equity, FC is still far below several other local coffee shops, which has an impact on the lack of purchase intention. To strengthen the brand and increase purchase intention, FC also actively carries out a co-branding strategy and promotes it on Instagram. The purpose of this study is to gain an understanding of the perceptions of FC’s Instagram followers towards the application of co-branding at FC and to determine the effect of co-branding on the purchase intention of FC’s Instagram followers. This study uses a quantitative design with 70 respondents who were selected using simple random sampling technique. The data analysis technique applied is quantitative descriptive analysis and simple linear regression analysis. The results of this study found that (1) Overall, the perception of FC’s Instagram followers towards co-branding is in the very good category. (2) Co-branding has a significant and positive effect on the purchase intention of FC’s Instagram followers. Suggestions for companies that they can add other promotional strategies that can attract consumers to always make repeat purchases at FC, and for further research can add other independent variables that can be studied at FC.